ANALISIS NILAI KOHESI DAN KOHERENSIDALAM TERJEMAHAN AL-QUR’AN SURAH AL AL ZALZALAH - MUNIRAH MUNIRAH; HUSAIN SYARIFUDDIN (JURNAL KONFIKS, 2014)
This study aimed to describe the value of cohesion and coherence contained in the translation of the Qur'an surah Al Zalzalah. This study was a qualitative descriptive research, research data collection techniques using three techniques namely, inventory, rading and understanding, and record keeping. The data analysis used the coding of data, classification data, and the determination of the data. The results showed that the cohesion markers used in the translation of surah Al Zalzalah discourse are: 1) reference, 2) pronouns, ie pronouns second person, and third, the relative pronoun, the pronoun pointer, pen pronouns and pronouns owner, 3 ) conjunctions, namely temporal conjunctions, coordinating conjunctions, subordinating conjunctions, and conjunctions koorelatif, and 4) a causal ellipsis. It mean that there was a coherence in the translation of surah Al Zalzalah discourse are: the addition or addition, pronouns, repetition or repetition, match words or synonyms, in whole or in part, a comparison or ratio of conclusions or results. Keywords: Cohesion, Coherence, sura Al Zalzalah AbstrakPenelitian ini bertujuan untuk mendeskripsikan nilai kohesi dan koherensi yang terdapat dalam terjemahan Al-Qur’an surah Al Zalzalah. Jenis penelitian ini termasuk jenis penelitian deskriptif kualitatif, Teknik pengumpulan data penelitian menggunakan tiga teknik yakni, inventarisasi, baca simak, dan pencatatan. Teknik analisis data menggunakan pengodean data, pengklasifikasian data, dan penentuan data. Hasil penelitian menunjukkan bahwa pemarkah kohesi yang digunakan dalam wacana terjemahan surah Al Zalzalah adalah: 1) referensi, 2) pronomina, yaitu kata ganti orang kedua, dan ketiga, kata ganti penghubung, kata ganti penunjuk, kata ganti penanya dan kata ganti empunya, 3) konjungsi, yaitu konjungsi temporal, konjungsi koordinatif, konjungsi subordinatif, dan konjungsi koorelatif, dan 4) elipsis kausal. Sarana koherensi yang terdapat di dalam wacana terjemahan surah Al Zalzalah adalah: penambahan atau adisi, pronomina, pengulangan atau repetisi, padan kata atau sinonim, keseluruhan atau bagian, komparasi atau perbandingan simpulan atau hasil.Kata Kunci: Kohesi, Koherensi, surah Al Zalzalah